Gambling disorder: a case report (Bangladesh Journal of Psychiatry, 2020)
Although gambling is a form of amusement for many people, some of them develop a gambling pattern marked by a lack of control, chasing losses, falsehoods and unlawful conduct. A case of gambling disorder was illustrated here who was presented with excessive involvement in gambling, continually losing money despite financial crisis and frequent unsuccessful attempts to control and stop gambling. He was treated with a combination of pharmacological and psychological interventions. Motivational interview, cognitive behavioral therapy and family therapy were mostly given and he showed considerable improvement within short period of treatment. Further studies should be conducted to explore more effective ways of managing the disorder.Bang J Psychiatry 2020; 34(1):18-19